Desempenho prognóstico da ferritina sérica em pacientes pediátricos com sepse admitidos na Unidade de Terapia Intensiva Pediátrica - Tonial, Cristian Tedesco (2020)
Introduction: Sepsis remains a high mortality disease worldwide. Prognostic markers are useful tools for targeting resources, indicating close monitoring or predicting early deterioration. Objective: To evaluate the prognostic performance of serum ferritin alone and in comparison with the Paediatric Index of Mortality 2 (PIM2) score, lactate, c-reactive protein (CRP) and total leukocytes in patients admitted to the Pediatric Intensive Care Unit (PICU). ) from a middle-income country with a high prevalence of iron deficiency anemia. Methods: Retrospective study conducted in a tertiary PICU in Brazil. Patients aged 6 months to 18 years admitted between June 2013 and January 2017 with a diagnosis of sepsis were selected. Ferritin and CRP values were collected in the first 48 hours, and lactate and leukocyte values in the first 24 hours after PICU admission. A detailed analysis was performed for serum ferritin. Demographic, clinical and outcome characteristics were collected from all patients and prognostic markers were compared using ROC curves and cutoff points obtained by the Youden Index. Results: During the study period there were 1407 admissions. Of these, 350 met the inclusion criteria. Ferritin was obtained from 312 patients and proved to be a good prognostic marker. Ferritin values were lower than previous studies, probably due to the high prevalence of iron deficiency anemia. Comparing the prognostic markers, PIM2, ferritin and lactate had similar performance. The PCR was slightly lower. The total leukocyte value was not useful as a prognostic marker. Conclusion: PIM2, ferritin, lactate and CRP showed good prognostic performance in patients with sepsis admitted to our PICU sample. The total leukocyte value was not useful for this purpose.